Functional proteomics and correlated signaling pathway of the thermophilic bacterium Bacillus stearothermophilus TLS33 under cold-shock stress - Topanurak S. (2014)
The thermophilic bacterium Bacillus stearothermophilus TLS33 was examined under cold-shock stress by a proteomic approach to gain a better understanding of the protein synthesis and complex regulatory pathways of bacterial adaptation. After downshift in the temperature from 65°C, the optimal growth temperature for this bacterium, to 37°C and 25°C for 2 h, we used the high-throughput techniques of proteomic analysis combining 2-DE and MS to identify 53 individual proteins including differentially expressed proteins. The bioinformatics database was used to search the biological functions of proteins and correlate these with gene homology and metabolic pathways in cell protection and adaptation. Eight cold-shock-induced proteins were shown to have markedly different protein expression: glucosyltransferase, anti-sigma B (σB) factor, Mrp protein homolog, dihydroorthase, hypothetical transcriptional regulator in FeuA-SigW intergenic region, RibT protein, phosphoadenosine phosphosulfate reductase and prespore-specific transcriptional activator RsfA. Interestingly, six of these cold-shock-induced proteins are correlated with the signal transduction pathway of bacterial sporulation. This study aims to provide a better understanding of the functional adaptation of this bacterium to environmental cold-shock stress. © 2005 WILEY-VCH Verlag GmbH & Co. KGaA.